A Bibliometric Analysis of Mathematics Education Research in Elementary Schools: Trends, Institutions, and Post-Pandemic Learning Integration (2020–2025) - Lola Aprianda; Karsoni Berta Dinata (ZERO: Jurnal Sains, Matematika dan Terapan, 2026)
Research on elementary mathematics education in the post pandemic period reflects changes in publication patterns and research topics. This study aims to analyze publication trends, institutional contributions, and forms of learning integration in elementary mathematics education research published between 2020 and 2025. The method employed is a bibliometric analysis of 921 Scopus-indexed articles using RStudio. The analysis covers annual publication trends, institutional productivity, authors’ geographical distribution, keyword-based thematic clusters, and citation patterns. The results show variations in annual publication output, with an increasing trend observed since 2023. Monash University and Universitas Negeri Yogyakarta are identified as the institutions with the highest publication output. Cluster analysis identifies three main thematic groups: student-oriented and numeracy-focused research, studies related to methodological approaches and teacher development, and research concerning pedagogy and curriculum. These findings describe the characteristics and thematic distribution of post pandemic research in elementary mathematics education.